The Assessment of Attitude, Knowledge, and Skill in English Language Learning on 2013 Curriculum: Yogi Saputra, Muhammad Yamin, Zaenuddin - Yogi Saputra (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2023)
This study aims to describe theoretically attitude assessment, knowledge assessment, and skills assessment. The method used in this discussion is the literature review method. This method emphasizes textbooks as a source of data and theoretical studies. The results of this discussion found that attitude assessment includes: (1) spiritual assessment in which there is religion and morality, (2) social assessment in which there is discipline, responsibility, courtesy, honesty, tolerance, and self-confidence. For the assessment of knowledge includes: (1) written tests in which there are multiple-choice tests, description tests, and false correct tests, (2) oral tests in which there are quizzes and questions and answers, (3) assignment tests in which there are group and individual tests both in school and outside of school, (4) portfolio and observation tests. For skills, the assessment includes (1) an assessment of practice in which there is reading, writing practice, and listening practice, (2) a project-based assessment in which there is interest and creativity, (3) a portfolio assessment, and (4) an Instrument assessment